DEVELOPMENT, OPTIMISATION AND THE ORGANOLEPTIC PROPERTIES OF EXTRUDED SORGHUM-BASED GLUTEN-FREE PASTA - Chopera, Prosper; Gwekwe, Blessing; Matsungo, Tonderayi M; Nyanga, Loveness K; Chidewe, Cathrine; Mukanganyama, Stanley; Nyakudya, Elijah; Mtambanengwe, Florence; Mapfumo, Paul (Food and Feed Research, 2024)
Pasta is one of the most consumed staples worldwide. New formulations incorporating novel nutritious ingredients are now common in its production. The purpose of this study was to formulate, optimise and evaluate the organoleptic properties of a sorghum based extruded gluten free pasta. Sorghum flour, pearl millet flour, high iron bean flour (Biofortified NUA 45 beans) and Hermes potato flour were evaluated for proximate and micronutrient composition, formulated to produce pasta through extrusion process. Three sorghum-based pastas namely sorghum high bean pasta (Treatment SHBP), sorghum bean pasta (Treatment SBP) and sorghum high potato pasta (Treatment SHPP) were produced and evaluated for sensorial properties (visual, palpatory and gustatory qualities). The Box Benhken Design (BBD) in conjunction with Response Surface Methodology (RSM) was used to select the best formulation by evaluating cooking quality parameters and organoleptic parameters. The protein content in the four flours ranged from 10.52% to 22%. NUA 45 bean flour had significantly (p<0.05) higher protein content than the other flours. Potato flour had significantly higher carbohydrate content (73.82%) as compared to other flours. Treatment SHPP had significantly (p<0.001) higher optimum cooking time (OCT) 7 minutes than Treatment SHBP 5 minutes and Treatment SBP 6.2 minutes. Treatment SHPP had significantly(p<0.001) higher water absorption (WA) capacity (238%) as compared to pasta Treatment SHBP (190%) and Treatment SBP (210%). Significant (p<0.001) difference in the swelling index (SI) of the three pasta treatments was observed with pasta Treatment SHBP having a significantly lower SI (1.02%) than Treatment SBP (1.15%) and Treatment SHPP (1.24%). The cooking loss (CL) for pasta Treatment SHPP (11%) was significantly higher (P<0.001) than for Treatment SHBP and SBP, with Treatment SHBP having the lowest CL. There was no significant (p>0.05) difference in the cross-sectional area, surface appearance and surface property of the three cooked pasta treatments. Significant (p<0.05) difference in shape between Treatment SHBP and SBP was noted. No significant (p>0.05) difference in surface property, cross-sectional area and surface appearance ranking of the three produced pasta. The gluten free pasta was developed and produced successfully. Sorghum high potato pasta treatment SHPP was found to be superior in terms of sensory, nutritional and physical properties as compared to the other pasta treatments hence good for commercialisation